A STUDY OF REGULAR STUDENTS’ SOCIAL SUPPORT FOR STUDENTS WITH SPECIAL NEEDS: HOW DOES IT RELATE TO SOCIAL ACCEPTANCE? - Damas, Fauzia Lazuardi; Kabbaro, Hurriyyatun; Faesal, Muhammad (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2025)
Abstract The implementation of inclusive education in Indonesia is still a challenge. Not all students with special needs are treated well by regular students. Students with special needs need social support in carrying out the learning process in inclusive schools. More studies need to be conducted on the social acceptance of regular students towards students with special needs. This study analyses the relationship between social acceptance and social support of regular students towards students with special needs. This research uses a correlational quantitative approach. Research data were collected using a proportionate stratified random sampling technique. The sample of this study totaled 209 regular students at SMP N 259 Jakarta, grades 7, 8, and 9, in whose classes there were students with special needs. Data collection used a questionnaire guided by the researcher. The instrument used to measure social acceptance consists of 21 items, while the instrument used to measure social support consists of 20 items. The results showed a correlation coefficient (r) of 0.832. This result means that the relationship between social acceptance and social support of regular students towards students with special needs is significant. So, the higher the social acceptance, the higher the social support. There needs to be socialization about inclusive education to encourage social acceptance of students with special needs. That way, social support will also increase.   Abstrak Implementasi pendidikan inklusi di Indonesia masih menjadi tantangan. Tidak semua siswa berkebutuhan khusus diperlakukan dengan baik oleh siswa reguler. Siswa berkebutuhan khusus membutuhkan dukungan sosial dalam menjalankan proses pembelajaran di sekolah inklusi. Perlu dilakukan penelitian lebih lanjut mengenai penerimaan sosial siswa reguler terhadap siswa berkebutuhan khusus. Penelitian ini menganalisis hubungan antara penerimaan sosial dan dukungan sosial siswa reguler terhadap siswa berkebutuhan khusus. Penelitian ini menggunakan pendekatan kuantitatif korelasional. Data penelitian dikumpulkan dengan menggunakan teknik proportionate stratified random sampling. Sampel penelitian ini berjumlah 209 siswa reguler di SMP N 259 Jakarta, kelas 7, 8, dan 9, yang di dalam kelasnya terdapat siswa berkebutuhan khusus. Pengumpulan data menggunakan kuesioner yang dipandu oleh peneliti. Instrumen yang digunakan untuk mengukur penerimaan sosial terdiri dari 21 item, sedangkan instrumen yang digunakan untuk mengukur dukungan sosial terdiri dari 20 item. Hasil penelitian menunjukkan koefisien korelasi (r) sebesar 0,832. Hasil ini berarti hubungan antara penerimaan sosial dan dukungan sosial siswa reguler terhadap siswa berkebutuhan khusus adalah signifikan. Jadi, semakin tinggi penerimaan sosial maka semakin tinggi pula dukungan sosialnya. Perlu adanya sosialisasi mengenai pendidikan inklusi untuk mendorong penerimaan sosial terhadap siswa berkebutuhan khusus. Dengan begitu, dukungan sosial juga akan meningkat.